2005
DOI: 10.1159/000087723
|View full text |Cite
|
Sign up to set email alerts
|

Overweight and Obesity among Schoolchildren in Sana’a City, Yemen

Abstract: Aim: To estimate the prevalence of overweight and obesity among schoolchildren in Sana’a City (Yemen) and to examine the association with lifestyle and some socioeconomic factors. Methods: A cross-sectional study was done in public and private schools in Sana’a City during 2002–2003. We selected 1,253 students by the multistage random sampling technique. Weights and heights were measured to calculate body mass index (BMI = weight/height2). Data about age, sex, education level of the parents, food co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
13
2

Year Published

2006
2006
2022
2022

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 24 publications
(15 citation statements)
references
References 25 publications
0
13
2
Order By: Relevance
“…In one study, the prevalence of overweight and obesity was positively associated with the educational level of the father and private schooling (52), while in this study it showed no association with neither of these.…”
Section: Discussioncontrasting
confidence: 71%
“…In one study, the prevalence of overweight and obesity was positively associated with the educational level of the father and private schooling (52), while in this study it showed no association with neither of these.…”
Section: Discussioncontrasting
confidence: 71%
“…A high prevalence, similar to that in developed countries, has been reported from countries like Mexico,14 Brazil,15 Qatar,16 the United Arab Emirates,17 and Kuwait 18. In contrast, a low prevalence has been reported from India (4.9% in 2003 and 6.6% in 2005 for overweight)19 and Yemen (6.2% for overweight and and 1.8% for obesity in 2002-2003 for school children) 20. In Saudi Arabia, reports on the prevalence of overweight and obesity were limited to male school children and a single city 21–23.…”
mentioning
confidence: 62%
“…, 2002; Mikkila et al. , 2003; Fonseca & de Matos, 2005; Raja’a et al. , 2005; Veugelers & Fitzgerald, 2005; Wong et al.…”
Section: Discussionmentioning
confidence: 99%